Exhaustion Experiences in Junior Athletes: The Importance of Motivation and Self-Control Competencies - Jordalen, Gro; Lemyre, Pierre-Nicolas; Durand-Bush, Natalie (Frontiers in Psychology, 2016)
Quality of motivation, self-control competencies, as well as past performance experience influence sport participation outcomes in developing athletes. Studies have shown that junior athletes high in self-determined motivation are less prone to experience burnout, while self-control competencies help developing athletes to be conscious and deliberate in their self-regulatory efforts toward elite sport performances and avoid negative sport participation outcomes. Combining the self-determination theory (SDT) framework and psychosocial theories of self-regulation, the aim of this cross-sectional study was to examine how various types of motivation and self-control competencies together are associated with the development of burnout symptoms in junior athletes. High-level Norwegian winter-sport athletes from elite sport academies (N = 199; female n = 72; 16 to 20 years of age) consented to participate. Associations between six types of motivational regulation, self-control, and indices of exhaustion were investigated. We hypothesized that athletes’ self-control competencies are important to operate successfully, and influenced by different types of motivation, they are expected to help athletes avoid negative sport participation outcomes such as emotional and physical exhaustion. Structural equation modeling analyses were conducted to analyze these relationships, and results revealed some multifaceted associations. When identifying antecedents of sport participation exhaustion and burnout, there is a need to go beyond the unique framework of motivation theories, and explore what cognitive competencies ensure fulfillment of motivation desires. In the current study, differences in junior athletes’ quality of motivation influenced self-control competencies when predicting exhaustion. Interestingly, young athletes driven by self-determined (intrinsic, integrated, and identified), and controlled (introjected and amotivation) regulations in association with self-control offered the strongest negative and positive associations with exhaustion, respectively. Findings clearly indicate that motivation and self-control competencies are meaningfully interrelated when assessing burnout propensity in young developing athletes.